The science of an avalanche - Hand, Carol, 1945- (21st century skills library. Disaster science., 2016)
"This book discusses the science behind avalanches and their effects. The chapters explore case studies of avalanches, identify environmental factors that cause these disasters, and explain how experts prevent avalanches. Diagrams, charts, and photos provide opportunities to evaluate and understand the scientific concepts involved."--Provided by publisher.